Local drug delivery to the bone by drug-releasing implants: perspectives of nano-engineered titania nanotube arrays. (July 2012) - Gulati, Karan; Aw, Moom Sinn; Findlay, David; Losic, Dusan
Titania nanotube (TNT) arrays fabricated by electrochemical anodization of titanium are currently one of the most attractive nanomaterials due to their remarkable properties. In this review, we highlight recent research activities that are focused on the application of the TNT arrays for local drug delivery, specifically for addressing problems associated with orthopedic implants. The advantages of drug-releasing implants based on TNT arrays for local delivery of therapeutics in bone related to these challenging problems including inflammation, infection and osseointegration are discussed. An overview of recent research to advance the drug-releasing performance of TNT arrays and the potential of their future applications and development are presented.